Participatory Land Use Planning in Pastoral Areas in Tanzania: IPSR Innovation Package and Scaling Readiness Report - Kang'ethe, Edwin; Flintan, Fiona E. (International Livestock Research Institute, 2022)
This is a report on a packaging exercise for the Tanzania land use planning innovation. It covers the evaluation process for Tanzania's readiness and use of innovative land use planning. The reports include identifying and selecting key solutions and activities necessary to scale the innovation and key actions needed to enhance the readiness and use of these key activities.